Unraveling the mechanistic origins of epoxy degradation in acids - Lim, Jacob Song Kiat (2020)
Water diffusion into polymers like thermosetting epoxies is well-studied; however, comparably little has been reported thus far on the related but very different mechanism of acid diffusion and the corresponding influence on material degradation. The diffusion of hydrochloric acid into an amine-cured epoxy system was studied in this work using gravimetric analysis and dielectric monitoring concurrently, and the mass uptake behavior was observed to differ significantly compared with water diffusion, faster by an order of magnitude. A unique 3-stage diffusion of acid into epoxy was observed due to the influence of Coulombic interactions between oppositely charged ionic species diffusing at different rates. Material characterization studies have revealed that the dominant degradation mechanism is physical in nature, with the formation of surface cracks driven by the swelling stresses due to the core-shell swelling behavior in highly concentrated hydrochloric acid, leading to an erosion-type degradation phenomenon. The insights gained from understanding acid electrolyte diffusion could serve to design a more effective and efficient process to enable thermoset recycling by facilitating rapid material breakdown or the design of acid-resistant materials for various applications in chemical storage tanks, batteries, and protective coatings in a corrosive environment.